Alpha rhythms in audition: Cognitive and clinical perspectives - Weisz, Nathan; Hartmann, Thomas; Müller, Nadia; Lorenz, Isabel; Obleser, Jonas (Frontiers in Psychology, 2011)
Like the visual and the sensorimotor systems, the auditory system exhibits pronounced alphalike resting oscillatory activity. Due to the relatively small spatial extent of auditory cortical areas, this rhythmic activity is less obvious and frequently masked by non-auditory alpha-generators when recording non-invasively using magnetoencephalography (MEG) or electroencephalography (EEG). Following stimulation with sounds, marked desynchronizations can be observed between 6 and 12 Hz, which can be localized to the auditory cortex. However knowledge about the functional relevance of the auditory alpha rhythm has remained scarce so far. Results from the visual and sensorimotor system have fuelled the hypothesis of alpha activity reflecting a state of functional inhibition. The current article pursues several intentions: (1) Firstly we review and present own evidence (MEG, EEG, sEEG) for the existence of an auditory alpha-like rhythm independent of visual or motor generators, something that is occasionally met with skepticism. (2) In a second part we will discuss tinnitus and how this audiological symptom may relate to reduced background alpha. The clinical part will give an introduction into a method which aims to modulate neurophysiological activity hypothesized to underlie this distressing disorder. Using neurofeedback, one is able to directly target relevant oscillatory activity. Preliminary data point to a high potential of this approach for treating tinnitus. (3) Finally, in a cognitive neuroscientific part we will show that auditory alpha is modulated by anticipation/expectations with and without auditory stimulation. We will also introduce ideas and initial evidence that alpha oscillations are involved in the most complex capability of the auditory system, namely speech perception. The evidence presented in this article corroborates findings from other modalities, indicating that alpha-like activity functionally has an universal inhibitory role across sensory modalities. © 2011 Weisz, Hartmann, Müller, Lorenz and Obleser.
Created from Fastlane, Scopus look-up
Keywords: Alpha; Attention; Auditory; EEG; MEG; Speech; Tau; Tinnitus

Decreasing alpha flow releases task-specific processing paths - Hanna, Jeffrey; Kim, Cora; Rampp, Stefan; Buchfelder, Michael; Müller-Voggel, Nadia (Imaging Neuroscience, 2024)
Directing and maintaining attention toward relevant information and away from non-relevant information is a critical competence of higher-order nervous systems. Here, we used directed connectivity to investigate how the human brain prioritizes appropriate processing paths when participants are performing a behavioral task requiring attention in the visual or the auditory modality. We show that the efficient transfer of information relevant for the task is mediated by a region- and task-specific decrease of alpha band connectivity from the parietal and, in case a motor response is required, motor cortex to the relevant sensory cortices. Further, alpha-band connectivity modulations reliably predict alpha power modulations in the task-related sensory cortices, particularly where the task-irrelevant cortex is inhibited via local alpha power increases. We suggest that the task- and region-specific modulation of alpha-band connectivity in the present study is a basic neuronal mechanism orchestrating the allocation of task-relevant neuronal resources related to and possibly underlying the previously reported sensory alpha power modulations in association with the allocation of competing attentional resources.
CRIS-Team Scopus Importer:2025-07-10
Keywords: alpha; attention; directed connectivity; MEG; phase transfer entropy

Effects of individual alpha rTMS applied to the auditory cortex and its implications for the treatment of chronic tinnitus - Weisz, Nathan; Luechinger, Claudia; Thut, Gregor; Müller, Nadia (Human Brain Mapping, 2014)
An increasing amount of studies apply repetetive transcranial magnetic stimulation (rTMS) to treat chronic tinnitus, yet the neurophysiological impacts have remained largely obscure. Several studies show that endogenous brain rhythms may be enhanced via diverse brain stimulation techniques applying rhythmic stimulation. Here, we investigated in normal hearing participants whether application of rTMS (left auditory cortex) with an individualized alpha frequency was capable of increasing alpha activity in stimulated auditory regions in a sustained manner. Behavioral intensity discrimination performance worsened for the rTMS group as compared to Sham. Electroencephalography (EEG) data, however, clearly show that this functional inhibition is not accompanied by increases of auditory cortical alpha. Even though more pronounced power reductions for the rTMS group were observed at slower frequencies (delta to theta range) at stimulated and other sites of the left hemisphere, they were unrelated to behavioral changes. Our results also strongly suggest that the amount of power modulations at these slower frequencies is strongly dependent on pre-rTMS power, thus supporting current state-dependency notions. Strong relationships to behavioral changes were in particular observed for anterior cingulate cortex (ACC) beta power and posterior cingulate cortex (PCC) beta connectivity. Moreover, these beta band measures were strongly inter-related and when viewed together specifically sensitive to behavioral changes in the rTMS group. We conclude that currently alpha frequency rTMS is not a promising avenue for the treatment of chronic tinnitus and that beneficial effects could be mediated via nonauditory systems. Our study argues for the value of combined EEG-TMS studies when investigating the impacts of rTMS. © 2012 Wiley Periodicals, Inc.
Created from Fastlane, Scopus look-up
Keywords: Beamforming; EEG; Entrainment; Node degree; State-dependency

External noise removed from magnetoencephalographic signal using independent component analyses of reference channels - Hanna, Jeffrey; Kim, Cora; Müller-Voggel, Nadia (Journal of Neuroscience Methods, 2020)
Background: Many magnetoencephalographs (MEG) contain, in addition to data channels, a set of reference channels positioned relatively far from the head that provide information on magnetic fields not originating from the brain. This information is used to subtract sources of non-neural origin, with either geometrical or least mean squares (LMS) methods. LMS methods in particular tend to be biased toward more constant noise sources and are often unable to remove intermittent noise. New method: To better identify and eliminate external magnetic noise, we propose performing ICA directly on the MEG reference channels. This in most cases produces several components which are clear summaries of external noise sources with distinct spatio-temporal patterns. We present two algorithms for identifying and removing such noise components from the data which can in many cases significantly improve data quality. Results: We performed simulations using forward models that contained both brain sources and external noise sources. First, traditional LMS-based methods were applied. While this removed a large amount of noise, a significant portion still remained. In many cases, this portion could be removed using the proposed technique, with little to no false positives. Comparison with existing method(s): The proposed method removes significant amounts of noise to which existing LMS-based methods tend to be insensitive. Conclusions: The proposed method complements and extends traditional reference based noise correction with little extra computational cost and low chances of false positives. Any MEG system with reference channels could profit from its use, particularly in labs with intermittent noise sources.
CRIS-Team Scopus Importer:2020-02-14
Keywords: ICA; Magnetoencephalography; Simulation

Higher Peripheral Inflammation Is Associated With Lower Orbitofrontal Gamma Power in Chronic Tinnitus - Becker, Linda; Keck, Antonia; Rohleder, Nicolas; Müller-Voggel, Nadia (Frontiers in Behavioral Neuroscience, 2022)
Chronic tinnitus, the continuous perception of a phantom sound, is a highly prevalent audiological symptom, for which the underlying pathology has not yet been fully understood. It is associated with neurophysiological alterations in the central nervous system and chronic stress, which can be related with a disinhibition of the inflammatory system. We here investigated the association between resting-state oscillatory activity assessed with Magnetoencephalography (MEG), and peripheral inflammation assessed by C-reactive protein (CRP) in a group of patients with chronic tinnitus (N = 21, nine males, mean age: 40.6 ± 14.6 years). Additionally, CRP was assessed in an age- and sex-matched healthy control group (N = 21, nine males, mean age: 40.9 ± 15.2 years). No MEG data was available for the control group. We found a significant negative correlation between CRP and gamma power in the orbitofrontal cortex in tinnitus patients (p < 0.001), pointing to a deactivation of the orbitofrontal cortex when CRP was high. No significant clusters were found for other frequency bands. Moreover, CRP levels were significantly higher in the tinnitus group than in the healthy controls (p = 0.045). Our results can be interpreted based on findings from previous studies having disclosed the orbitofrontal cortex as part of the tinnitus distress network. We suggest that higher CRP levels and the associated deactivation of the orbitofrontal cortex in chronic tinnitus patients is maintaining the tinnitus percept through disinhibition of the auditory cortex and attentional or emotional top-down processes. Although the direction of the association (i.e., causation) between CRP levels and orbitofrontal gamma power in chronic tinnitus is not yet known, inflammation reducing interventions are promising candidates when developing treatments for tinnitus patients. Overall, our study highlights the importance of considering immune-brain communication in tinnitus researc
Keywords: tinnitus; inflammation; MEG; C-reactive protein; stress; oscillatory activity

Interictal Electrical Source Imaging. - Rampp, Stefan; Müller-Voggel, Nadia; Hamer, Hajo; Dörfler, Arnd; Brandner, Sebastian; Buchfelder, Michael (Journal of Clinical Neurophysiology, 2024)
Interictal electrical source imaging (ESI) determines the neuronal generators of epileptic activity in EEG occurring outside of seizures. It uses computational models to take anatomic and neuronal characteristics of the individual patient into account. The presented article provides an overview of application and clinical value of interictal ESI in patients with pharmacoresistant focal epilepsies undergoing evaluation for surgery. Neurophysiological constraints of interictal data are discussed and technical considerations are summarized. Typical indications are covered as well as issues of integration into clinical routine. Finally, an outlook on novel markers of epilepsy for interictal source analysis is presented. Interictal ESI provides diagnostic performance on par with other established methods, such as MRI, PET, or SPECT. Although its accuracy benefits from high-density recordings, it provides valuable information already when applied to EEG with only a limited number of electrodes with complete coverage. Novel oscillatory markers and the integration of frequency coupling and connectivity may further improve accuracy and efficiency.
EVALuna2:547206

Lateralized auditory cortical alpha band activity and interregional connectivity pattern reflect anticipation of target sounds - Müller, Nadia; Weisz, Nathan (Cerebral Cortex, 2012)
The anticipation of stimuli facilitates the top-down preparation of neuronal tissue involved in the processing of forthcoming targets. Increasing evidence in the visual modality emphasizes the anticipatory adjustment of visual cortex excitability through modulations of oscillatory alpha power. In the auditory system, however, this relationship has not yet been established. Furthermore, the association between anticipatory modulations of auditory alpha power and a potential top-down network within these anticipatory preparation processes remains unexplained. To disclose these processes, we recorded magnetoencephalography while visually cuing participants to attend to either ear and to anticipate forthcoming auditory stimuli. For the cue-stimulus phase, we expected an asymmetric modulation of auditory alpha power when attending to the left or right ear, assuming that frontoparietal regions would phase synchronize with the auditory cortex in an asymmetric pattern. Beamformer source solutions demonstrate an asymmetric modulation of auditory alpha power following visual cues expressed in a strong right auditory alpha power increase when attending to the right ear. Furthermore, the right auditory cortex is functionally connected to the frontal eye fields during the ipsilateral alpha increase. Altogether, these results contribute significantly to the understanding of how auditory anticipation acts on a local as well as on a network level. © 2011 The Author.
Created from Fastlane, Scopus look-up
Keywords: frontal eye field; MEG; phase coupling; spatial attention; synchronization

Listen to yourself: The medial prefrontal cortex modulates auditory alpha power during speech preparation - Müller-Voggel, Nadia; Leske, Sabine; Hartmann, Thomas; Szebenyi, Szabolcs; Weisz, Nathan (Cerebral Cortex, 2015)
How do we process stimuli that stem from the external world and stimuli that are self-generated? In the case of voice perception it has been shown that evoked activity elicited by self-generated sounds is suppressed compared with the same sounds played-back externally. We here wanted to reveal whether neural excitability of the auditory cortex-putatively reflected in local alpha band power-is modulated already prior to speech onset, and which brain regions may mediate such a top-down preparatory response. In the left auditory cortex we show that the typical alpha suppression found when participants prepare to listen disappears when participants expect a selfspoken sound. This suggests an inhibitory adjustment of auditory cortical activity already before sound onset. As a second main finding we demonstrate that the medial prefrontal cortex, a region known for selfreferential processes, mediates these condition-specific alpha power modulations. This provides crucial insights into how higher-order regions prepare the auditory cortex for the processing of self-generated sounds. Furthermore, the mechanism outlined could provide further explanations to self-referential phenomena, such as "tickling yourself". Finally, it has implications for the so-far unsolved question of how auditory alpha power is mediated by higher-order regions in a more general sense.
Created from Fastlane, Scopus look-up
Keywords: Effective connectivity; Efference copy; MEG; Oscillation; Top-down

Localization of beta power decrease as measure for lateralization in pre-surgical language mapping with magnetoencephalography, compared with functional magnetic resonance imaging and validated by Wada test - Herfurth, Kirsten; Harpaz, Yuval; Rösch, Julie; Müller, Nadia; Walther, Katrin; Kaltenhaeuser, Martin; Pauli, Elisabeth; Goldstein, Abraham; Hamer, Hajo; Buchfelder, Michael; Dörfler, Arnd; Prell, Julian; et al. (Frontiers in Human Neuroscience, 2022)
Objective: Atypical patterns of language lateralization due to early reorganizational processes constitute a challenge in the pre-surgical evaluation of patients with pharmaco-resistant epilepsy. There is no consensus on an optimal analysis method used for the identification of language dominance in MEG. This study examines the concordance between MEG source localization of beta power desynchronization and fMRI with regard to lateralization and localization of expressive and receptive language areas using a visual verb generation task. Methods: Twenty-five patients with pharmaco-resistant epilepsy, including six patients with atypical language lateralization, and ten right-handed controls obtained MEG and fMRI language assessment. Fourteen patients additionally underwent the Wada test. We analyzed MEG beta power desynchronization in sensor (controls) and source space (patients and controls). Beta power decrease between 13 and 35 Hz was localized applying Dynamic Imaging of Coherent Sources Beamformer technique. Statistical inferences were grounded on cluster-based permutation testing for single subjects. Results: Event-related desynchronization of beta power in MEG was seen within the language-dominant frontal and temporal lobe and within the premotor cortex. Our analysis pipeline consistently yielded left language dominance with high laterality indices in controls. Language lateralization in MEG and Wada test agreed in all 14 patients for inferior frontal, temporal and parietal language areas (Cohen’s Kappa = 1, p < 0.001). fMRI agreed with Wada test in 12 out of 14 cases (85.7%) for Broca’s area (Cohen’s Kappa = 0.71, p = 0.024), while the agreement for temporal and temporo-parietal language areas were non-significant. Concordance between MEG and fMRI laterality indices was highest within the inferior frontal gyrus, with an agreement in 19/24 cases (79.2%), and non-significant for Wernicke’s area. Spatial agreement between fMRI and MEG varied considerably between subjects and brain regions with the lowest Euclidean distances within the inferior frontal region of interest. Conclusion: Localizing the desynchronization of MEG beta power using a verb generation task is a promising tool for the identification of language dominance in the pre-surgical evaluation of epilepsy patients. The overall agreement between MEG and fMRI was lower than expected and might be attributed to differences within the baseline condition. A larger sample size and an adjustment of the experimental designs are needed to draw further conclusions.
CRIS-Team Scopus Importer:2022-11-25
Keywords: beta power decrease; epilepsy; epilepsy surgery; functional magnetic resonance imaging (fMRI); intracarotid sodium amobarbital procedure (IAT); language lateralization; magnetoencephalography (MEG); Wada test

Loss of alpha power is related to increased gamma synchronization-A marker of reduced inhibition in tinnitus? - Lorenz, Isabel; Müller, Nadia; Schlee, Winfried; Hartmann, Thomas; Weisz, Nathan (Neuroscience Letters, 2009)
Tinnitus is the perception of sound in the absence of any external auditory stimulus. Based on previous research we have proposed a framework which postulates that the reduction of ongoing inhibitory alpha activity in tinnitus subjects favors a synchronization of neurons in the gamma frequency range while in a resting state. In the present work we are validating the existence of an inverse relationship between auditory gamma and alpha activity in tinnitus and control subjects using Magnetoencephalography. Tinnitus subjects exhibited a significantly steeper slope of the regression line compared to controls, presumably because a greater number of subjects concurrently exhibited low alpha and high gamma power. Therefore, the role of the alpha-gamma pattern is discussed regarding its possible implication for the generation of tinnitus. © 2009 Elsevier Ireland Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Alpha; Gamma; Magnetoencephalography; Oscillatory brain activity; Tinnitus

Mapping cortical hubs in tinnitus - Schlee, Winfried; Müller, Nadia; Hartmann, Thomas; Keil, Julian; Lorenz, Isabel; Weisz, Nathan (BMC Biology, 2009)
Background: Subjective tinnitus is the perception of a sound in the absence of any physical source. It has been shown that tinnitus is associated with hyperactivity of the auditory cortices. Accompanying this hyperactivity, changes in non-auditory brain structures have also been reported. However, there have been no studies on the long-range information flow between these regions. Results: Using Magnetoencephalography, we investigated the long-range cortical networks of chronic tinnitus sufferers (n = 23) and healthy controls (n = 24) in the resting state. A beamforming technique was applied to reconstruct the brain activity at source level and the directed functional coupling between all voxels was analyzed by means of Partial Directed Coherence. Within a cortical network, hubs are brain structures that either influence a great number of other brain regions or that are influenced by a great number of other brain regions. By mapping the cortical hubs in tinnitus and controls we report fundamental group differences in the global networks, mainly in the gamma frequency range. The prefrontal cortex, the orbitofrontal cortex and the parieto-occipital region were core structures in this network. The information flow from the global network to the temporal cortex correlated positively with the strength of tinnitus distress. Conclusion: With the present study we suggest that the hyperactivity of the temporal cortices in tinnitus is integrated in a global network of long-range cortical connectivity. Top-down influence from the global network on the temporal areas relates to the subjective strength of the tinnitus distress. © 2009 Schlee et al; licensee BioMed Central Ltd.
Created from Fastlane, Scopus look-up

MEG Node Degree Differences in Patients with Focal Epilepsy vs. Controls-Influence of Experimental Conditions - Vogel, Stephan; Kaltenhaeuser, Martin; Kim, Cora; Müller-Voggel, Nadia; Rössler, Karl; Dörfler, Arnd; Schwab, Stefan; Hamer, Hajo; Buchfelder, Michael; Rampp, Stefan (Brain Sciences, 2021)
Drug-resistant epilepsy can be most limiting for patients, and surgery represents a viable therapy option. With the growing research on the human connectome and the evidence of epilepsy being a network disorder, connectivity analysis may be able to contribute to our understanding of epilepsy and may be potentially developed into clinical applications. In this magnetoencephalographic study, we determined the whole-brain node degree of connectivity levels in patients and controls. Resting-state activity was measured at five frequency bands in 15 healthy controls and 15 patients with focal epilepsy of different etiologies. The whole-brain all-to-all imaginary part of coherence in source space was then calculated. Node degree was determined and parcellated and was used for further statistical evaluation. In comparison to controls, we found a significantly higher overall node degree in patients with lesional and non-lesional epilepsy. Furthermore, we examined the conditions of high/reduced vigilance and open/closed eyes in controls, to analyze whether patient node degree levels can be achieved. We evaluated intraclass-correlation statistics (ICC) to evaluate the reproducibility. Connectivity and specifically node degree analysis could present new tools for one of the most common neurological diseases, with potential applications in epilepsy diagnostics.
CRIS-Team WoS Importer:2022-01-07

MEG Node Degree for Focus Localization: Comparison with Invasive EEG - Rampp, Stefan; Kaltenhaeuser, Martin; Müller-Voggel, Nadia; Dörfler, Arnd; Kasper, Burkhard S.; Hamer, Hajo; Brandner, Sebastian; Buchfelder, Michael (Biomedicines, 2023)
Epilepsy surgery is a viable therapy option for patients with pharmacoresistant focal epilepsies. A prerequisite for postoperative seizure freedom is the localization of the epileptogenic zone, e.g., using electro- and magnetoencephalography (EEG/MEG). Evidence shows that resting state MEG contains subtle alterations, which may add information to the workup of epilepsy surgery. Here, we investigate node degree (ND), a graph-theoretical parameter of functional connectivity, in relation to the seizure onset zone (SOZ) determined by invasive EEG (iEEG) in a consecutive series of 50 adult patients. Resting state data were subjected to whole brain, all-to-all connectivity analysis using the imaginary part of coherence. Graphs were described using parcellated ND. SOZ localization was investigated on a lobar and sublobar level. On a lobar level, all frequency bands except alpha showed significantly higher maximal ND (mND) values inside the SOZ compared to outside (ratios 1.11-1.20, alpha 1.02). Area-under-the-curve (AUC) was 0.67-0.78 for all expected alpha (0.44, ns). On a sublobar level, mND inside the SOZ was higher for all frequency bands (1.13-1.38, AUC 0.58-0.78) except gamma (1.02). MEG ND is significantly related to SOZ in delta, theta and beta bands. ND may provide new localization tools for presurgical evaluation of epilepsy surgery.
CRIS-Team WoS Importer:2023-03-24
Keywords: MEG; epilepsy; epilepsy surgery; connectivity; graph theory; focus localization

Now i am ready - Now i am not: The influence of pre-TMS oscillations and corticomuscular coherence on motor-evoked potentials - Schulz, Hannah; Uebelacker, Teresa; Keil, Julian; Müller, Nadia; Weisz, Nathan (Cerebral Cortex, 2014)
There is a growing body of research on the functional role of oscillatory brain activity. However, its relation to functional connectivity has remained largely obscure. In the sensorimotor system, movement-related changes emerge in the α (8-14 Hz) and β (15-30 Hz) range (event-related desynchronization, ERD, before and during movement; event-related synchronization, ERS, after movement offset). Some studies suggest that β-ERS may functionally inhibit new movements. According to the gating-by-inhibition framework (Jensen and Mazaheri 2010), we expected that the ERD would go along with increased corticomuscular coupling, and vice versa. By combining transcranial magnetic stimulation (TMS) and electroencephalography, we were directly able to test this hypothesis. In a reaction time task, single TMS pulses were delivered randomly during ERD/ERS to the motor cortex. The motor-evoked potential (MEP) was then related to the β and α frequencies and corticomuscular coherence. Results indicate that MEPs are smaller when preceded by high pre-TMS β-band power and low pre-TMS α-band corticomuscular coherence (and vice versa) in a network of motor-relevant areas comprising frontal, parietal, and motor cortices. This confirms that an increase in rhythms that putatively reflect functionally inhibited states goes along with weaker coupling of the respective brain regions. © 2013 The Author. Published by Oxford University Press. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: corticomuscular coherence; ERD/ERS; gating by inhibition; motor network; TMS

On the variability of the McGurk effect: Audiovisual integration depends on prestimulus brain states - Keil, Julian; Müller, Nadia; Ihssen, Niklas; Weisz, Nathan (Cerebral Cortex, 2012)
The McGurk effect demonstrates the influence of visual cues on auditory perception. Mismatching information from both sensory modalities can fuse to a novel percept that matches neither the auditory nor the visual stimulus. This illusion is reported in 60-80% of trials. We were interested in the impact of ongoing brain oscillations - indexed by fluctuating local excitability and interareal synchronization - on upcoming perception of identical stimuli. The perception of the McGurk effect is preceded by high beta activity in parietal, frontal, and temporal areas. Beta activity is pronounced in the left superior temporal gyrus (lSTG), which is considered as a site of multimodal integration. This area is functionally (de)coupled to distributed frontal and temporal regions in illusion trials. The disposition to fuse multisensory information is enhanced as the lSTG is more strongly coupled to frontoparietal regions. Illusory perception is accompanied by a decrease in poststimulus theta-band activity in the cuneus, precuneus, and left superior frontal gyrus. Event-related activity in the left middle temporal gyrus is pronounced during illusory perception. Thus, the McGurk effect depends on fluctuating brain states suggesting that functional connectedness of left STS at a prestimulus stage is crucial for an audiovisual percept. © The Author 2011. Published by Oxford University Press. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: illusion; MEG; multisensory; perception

Oscillatory alpha modulations in right auditory regions reflect the validity of acoustic cues in an auditory spatial attention task - Weisz, Nathan; Müller, Nadia; Jatzev, Sabine; Bertrand, Olivier (Cerebral Cortex, 2014)
Anticipation of targets in the left or right hemifield leads to alpha modulations in posterior brain areas. Recently using magnetoencephalography, we showed increased right auditory alpha activity when attention was cued ipsilaterally. Here, we investigated the issue how cue validity itself influences oscillatory alpha activity. Acoustic cues were presented either to the right or left ear, followed by a compound dichotically presented target plus distractor. The preceding cue was either informative (75% validity) or uninformative (50%) about the location of the upcoming target. Cue validity×siderelated alpha modulations were identified in pre- And posttarget periods in a right lateralized network, comprising auditory and nonauditory regions. This replicates and extends our previous finding of the right hemispheric dominance of auditory attentional modulations. Importantly, effective connectivity analysis showed that, in the pretarget period, this effect is accompanied by a pronounced and timevarying connectivity pattern of the right auditory cortex to the right intraparietal sulcus (IPS), with influence of IPS on superior temporal gyrus dominating at earlier intervals of the cue- Target period. Our study underlines the assumption that alpha oscillations may play a similar functional role in auditory cortical regions as reported in other sensory modalities and suggests that these effects may be mediated via IPS.
Created from Fastlane, Scopus look-up
Keywords: Alpha oscillations; Auditory cortex; Intraparietal sulcus; Magnetoencephalography; Spatial attention

Prestimulus beta power and phase synchrony influence the sound-induced flash illusion - Keil, Julian; Müller, Nadia; Hartmann, Thomas; Weisz, Nathan (Cerebral Cortex, 2014)
We investigated the sound-induced flash illusion, an example for the influence of auditory information on visual perception. It consists of the perception of 2 visual stimuli upon the presentation of a single visual stimulus alongside 2 auditory stimuli. We used magnetoencephalography to assess the influence of prestimulus oscillatory activity on varying the perception of invariant stimuli. We compared cortical activity from trials in which subjects perceived an illusion with trials in which subjects did not perceive the illusion, keeping the stimulation fixed. Subjects perceived the illusion in approximately 50% of trials. Prior to the illusion, we found stronger beta-band power in left temporal sensors, localized to the left middle temporal gyrus. Illusory perceptions were preceded by increased beta-band phase synchrony between the left middle temporal gyrus and auditory areas as well as by decreased phase synchrony with visual areas. Alpha-band phase synchrony between visual and temporal, parietal, and frontal cortical areas as well as alpha-band phase synchrony between auditory and visual areas were modulated. This supports and extends reports on the influence of brain states prior to stimulation on subsequent perception. We suggest that prestimulus local and network activities form predispositions if sensory streams will be integrated. © 2013 The Author.
Created from Fastlane, Scopus look-up
Keywords: audiovisual illusion; connectivity; magnetoencephalography; oscillatory activity; perception

Prestimulus feedback connectivity biases the content of visual experiences - Rassi, Elie; Wutz, Andreas; Müller-Voggel, Nadia; Weisz, Nathan (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Ongoing fluctuations in neural excitability and in networkwide activity patterns before stimulus onset have been proposed to underlie variability in near-threshold stimulus detection paradigms—that is, whether or not an object is perceived. Here, we investigated the impact of prestimulus neural fluctuations on the content of perception—that is, whether one or another object is perceived. We recorded neural activity with magnetoencephalography (MEG) before and while participants briefly viewed an ambiguous image, the Rubin face/vase illusion, and required them to report their perceived interpretation in each trial. Using multivariate pattern analysis, we showed robust decoding of the perceptual report during the poststimulus period. Applying source localization to the classifier weights suggested early recruitment of primary visual cortex (V1) and ∼160-ms recruitment of the category-sensitive fusiform face area (FFA). These poststimulus effects were accompanied by stronger oscillatory power in the gamma frequency band for face vs. vase reports. In prestimulus intervals, we found no differences in oscillatory power between face vs. vase reports in V1 or in FFA, indicating similar levels of neural excitability. Despite this, we found stronger connectivity between V1 and FFA before face reports for low-frequency oscillations. Specifically, the strength of prestimulus feedback connectivity (i.e., Granger causality) from FFA to V1 predicted not only the category of the upcoming percept but also the strength of poststimulus neural activity associated with the percept. Our work shows that prestimulus network states can help shape future processing in category-sensitive brain regions and in this way bias the content of visual experiences.
CRIS-Team Scopus Importer:2019-08-13
Keywords: Connectivity; MEG; Oscillations; Prestimulus; Visual object perception

Prestimulus network integration of auditory cortex predisposes near-threshold perception independently of local excitability - Leske, Sabine; Ruhnau, Philipp; Frey, Julia; Lithari, Chrysa; Müller-Voggel, Nadia; Hartmann, Thomas; Weisz, Nathan (Cerebral Cortex, 2015)
Created from Fastlane, Scopus look-up
Keywords: Auditory consciousness; Functional connectivity; Graph theory; MEG; Ongoing oscillations

Rapid increases of gamma power in the auditory cortex following noise trauma in humans - Ortmann, Magdalene; Müller, Nadia; Schlee, Winfried; Weisz, Nathan (European Journal of Neuroscience, 2011)
Tinnitus is an auditory perception in the absence of any external sound source. It has been suggested that tinnitus is related to enhanced synchronization of neuronal activity in the auditory cortex. Usually a hearing damage can be identified suggesting auditory deprivation to central auditory regions to be fundamental for neurophysiological processes related to tinnitus. Until now, human research has been conducted on patients with chronic tinnitus (>6months). However, neuronal activity accompanying auditory deprivation and putatively tinnitus may not remain constant over time, making it difficult to directly relate outcomes of current animal studies (acute tinnitus) to chronic tinnitus in humans, and vice versa. We investigated 14 amateur rock musicians who frequently reported a short-term tinnitus immediately after band practice. Magnetoencephalographic resting-state recordings, audiometry and tinnitus testing were performed at two separate occasions: with and without previous exposure to loud music. Analyses revealed that transient tinnitus was accompanied by temporary hearing loss in both ears and increased gamma activity in the right auditory cortex in 13 out of 14 cases. Additionally, tinnitus frequency was strongly correlated to hearing loss. Analogous to animal studies, our results show for the first time in humans that noise trauma leads rapidly to increased neuronal synchrony in the auditory cortex. Importantly, the strongly right-lateralized effect implies that it does not reflect tinnitus percept per se. This could rather have been triggered by greater discontinuities of hearing loss at high frequencies that were particularly pronounced in the left ear. © 2010 The Authors. European Journal of Neuroscience © 2010 Federation of European Neuroscience Societies and Blackwell Publishing Ltd.
Created from Fastlane, Scopus look-up
Keywords: Auditory cortex; Gamma; Hearing loss; MEG; Transient tinnitus

Reducing Tinnitus via Inhibitory Influence of the Sensorimotor System on Auditory Cortical Activity - Sabados, Anne; Kim, Cora; Rampp, Stefan; Bergherr, Elisabeth; Buchfelder, Michael; Schnell, Oliver; Müller-Voggel, Nadia (The Journal of Neuroscience, 2025)
Tinnitus is the subjective perception of a sound without corresponding external acoustic stimuli. Research highlights the influence of the sensorimotor system on tinnitus perception. Associated neuronal processes, however, are insufficiently understood, and it remains unclear how and at which hierarchical level the sensorimotor system interacts with the tinnitus-processing auditory system. We therefore asked 23 patients suffering from chronic tinnitus (11 males) to perform specific exercises, aimed at relaxing or tensing the jaw area, which temporarily modulated tinnitus perception. Associated neuronal processes were assessed using magnetencephalography. Results show that chronic tinnitus patients experienced their tinnitus as weaker and less annoying after completion of relaxing compared with tensing exercises. Furthermore, (1) sensorimotor alpha power and alpha-band connectivity directed from the somatosensory to the auditory cortex increased and (2) gamma power in the auditory cortex reduced, which (3) related to reduced tinnitus annoyance perception on a trial-by-trial basis in the relaxed state. No effects were revealed for 23 control participants without tinnitus (six males) performing the same experiment. We conclude that the increase in directed alpha-band connectivity from the somatosensory to the auditory cortex most likely reflects the transmission of inhibition from the somatosensory to the auditory cortex during relaxation, where concurrently tinnitus-related gamma power reduces. We suggest that revealed neuronal processes are transferable to other tinnitus-modulating systems beyond the sensorimotor one that is involved in attentional or emotional tinnitus modulation and provides deeper mechanistic insights into how and through which channels phantom sound perception might be modulated on a neuronal level.
CRIS-Team Scopus Importer:2025-05-02
Keywords: alpha; chronic tinnitus; connectivity; gamma; somatosensory; top-down

rTMS Induced Tinnitus Relief Is Related to an Increase in Auditory Cortical Alpha Activity - Müller, Nadia; Lorenz, Isabel; Langguth, Berthold; Weisz, Nathan (PLoS ONE, 2013)
Chronic tinnitus, the continuous perception of a phantom sound, is a highly prevalent audiological symptom. A promising approach for the treatment of tinnitus is repetitive transcranial magnetic stimulation (rTMS) as this directly affects tinnitus-related brain activity. Several studies indeed show tinnitus relief after rTMS, however effects are moderate and vary strongly across patients. This may be due to a lack of knowledge regarding how rTMS affects oscillatory activity in tinnitus sufferers and which modulations are associated with tinnitus relief. In the present study we examined the effects of five different stimulation protocols (including sham) by measuring tinnitus loudness and tinnitus-related brain activity with Magnetoencephalography before and after rTMS. Changes in oscillatory activity were analysed for the stimulated auditory cortex as well as for the entire brain regarding certain frequency bands of interest (delta, theta, alpha, gamma). In line with the literature the effects of rTMS on tinnitus loudness varied strongly across patients. This variability was also reflected in the rTMS effects on oscillatory activity. Importantly, strong reductions in tinnitus loudness were associated with increases in alpha power in the stimulated auditory cortex, while an unspecific decrease in gamma and alpha power, particularly in left frontal regions, was linked to an increase in tinnitus loudness. The identification of alpha power increase as main correlate for tinnitus reduction sheds further light on the pathophysiology of tinnitus. This will hopefully stimulate the development of more effective therapy approaches. © 2013 Müller et al.
Created from Fastlane, Scopus look-up

Selective modulation of auditory cortical alpha activity in an audiovisual spatial attention task - Frey, Julia N.; Mainy, Nelly; Lachaux, Jean-Philippe; Müller, Nadia; Bertrand, Olivier; Weisz, Nathan (Journal of Neuroscience, 2014)
Created from Fastlane, Scopus look-up

Short-term effects of single repetitive TMS sessions on auditory evoked activity in patients with chronic tinnitus - Lorenz, Isabel; Müller, Nadia; Schlee, Winfried; Langguth, Berthold; Weisz, Nathan (Journal of Neurophysiology, 2010)
Subjective tinnitus is the perception of a sound without any external source. Repetitive transcranial magnetic stimulation (rTMS) has been examined as a treatment tool for chronic tinnitus for several years trying to target hyperactivity/abnormal synchronization within the auditory cortex putatively underlying the auditory phantom percept. However, its exact impact on auditory cortical activity remains largely unknown. This study's objective was to systematically examine changes in auditory responses (N1, auditory steady-state response [aSSR]) measured by means of magnetoencephalography after single sessions of stimulation with different TMS paradigms. Subjects with chronic tinnitus (n = 10) underwent five sessions of rTMS in which they received one of five different stimulation protocols (1 Hz, individual alpha frequency, continuous theta burst stimulation [cTBS], intermittent theta burst stimulation [iTBS], and sham) in randomized order using a single-blind study design. Cortical steady-state responses to 40 Hz amplitude-modulated tones were measured before and after each magnetic stimulation protocol. The results demonstrate a reduction of the cortical response to the auditory steady-state stimulus after magnetic stimulation, whereas the N1 response was slightly enhanced or remained unchanged. Furthermore, reduction of the aSSR was driven by effects of iTBS, cTBS, and 1 Hz stimulation. Correspondingly, behavioral measures demonstrated the greatest reduction of tinnitus loudness after the respective rTMS protocols. The current study offers an interesting insight into the effects of rTMS on auditory cortical activity. The results of the study are discussed in the context of current limitations of TMS for the treatment of chronic tinnitus. Copyright © 2010 The American Physiological Society.
Created from Fastlane, Scopus look-up

The effects of neurofeedback on oscillatory processes related to tinnitus - Hartmann, Thomas; Lorenz, Isabel; Müller, Nadia; Langguth, Berthold; Weisz, Nathan (Brain Topography, 2014)
Although widely used, no proof exists for the feasibility of neurofeedback for reinstating the disordered excitatory-inhibitory balance, marked by a decrease in auditory alpha power, in tinnitus patients. The current study scrutinizes the ability of neurofeedback to focally increase alpha power in auditory areas in comparison to the more common rTMS. Resting-state MEG was measured before and after neurofeedback (n = 8) and rTMS (n = 9) intervention respectively. Source level power and functional connectivity were analyzed with a focus on the alpha band. Only neurofeedback produced a significant decrease in tinnitus symptoms and - more important for the context of the study - a spatially circumscribed increase in alpha power in right auditory regions. Connectivity analysis revealed higher outgoing connectivity in a region ultimately neighboring the area in which power increases were observed. Neurofeedback decreases tinnitus symptoms and increases alpha power in a spatially circumscribed manner. In addition, compared to a more established brain stimulation-based intervention, neurofeedback is a promising approach to renormalize the excitatory-inhibitory imbalance putatively underlying tinnitus. This study is the first to demonstrate the feasibility of focally enhancing alpha activity in tinnitus patients by means of neurofeedback. © 2013 Springer Science+Business Media New York.
Created from Fastlane, Scopus look-up
Keywords: Auditory alpha; MEG; Neurofeedback; rTMS; Tau rhythm; Tinnitus

The modulatory influence of a predictive cue on the auditory steady-state response - Weisz, Nathan; Lecaignard, Francoise; Müller, Nadia; Bertrand, Olivier (Human Brain Mapping, 2012)
Whether attention exerts its impact already on primary sensory levels is still a matter of debate. Particularly in the auditory domain the amount of empirical evidence is scarce. Recently noninvasive and invasive studies have shown attentional modulations of the auditory Steady-State Response (aSSR). This evoked oscillatory brain response is of importance to the issue, because the main generators have been shown to be located in primary auditory cortex. So far, the issue whether the aSSR is sensitive to the predictive value of a cue preceding a target has not been investigated. Participants in the present study had to indicate on which ear the faster amplitude modulated (AM) sound of a compound sound (42 and 19 Hz AM frequencies) was presented. A preceding auditory cue was either informative (75%) or uninformative (50%) with regards to the location of the target. Behaviorally we could confirm that typical attentional modulations of performance were present in case of a preceding informative cue. With regards to the aSSR we found differences between the informative and uninformative condition only when the cue/target combination was presented to the right ear. Source analysis indicated this difference to be generated by a reduced 42 Hz aSSR in right primary auditory cortex. Our and previous data by others show a default tendency of "40 Hz" AM sounds to be processed by the right auditory cortex. We interpret our results as active suppression of this automatic response pattern, when attention needs to be allocated to right ear input. © 2011 Wiley Periodicals, Inc.
Created from Fastlane, Scopus look-up
Keywords: Auditory cortex; Beamforming; MEG; Selective attention

The strength of alpha and beta oscillations parametrically scale with the strength of an illusory auditory percept - Leske, Sabine; Tse, Ada; Oosterhof, Nikolaas N.; Hartmann, Thomas; Müller, Nadia; Keil, Julian; Weisz, Nathan (NeuroImage, 2014)
Studies investigating the role of oscillatory activity in sensory perception are primarily conducted in the visual domain, while the contribution of oscillatory activity to auditory perception is heavily understudied. The objective of the present study was to investigate macroscopic (EEG) oscillatory brain response patterns that contribute to an auditory (Zwicker tone, ZT) illusion. Three different analysis approaches were chosen: 1) a parametric variation of the ZT illusion intensity via three different notch widths of the ZT-inducing noise; 2) contrasts of high-versus-low-intensity ZT illusion trials, excluding physical stimuli differences; 3) a representational similarity analysis to relate source activity patterns to loudness ratings. Depending on the analysis approach, levels of alpha to beta activity (10-20. Hz) reflected illusion intensity, mainly defined by reduced power levels co-occurring with stronger percepts. Consistent across all analysis approaches, source level analysis implicated auditory cortices as main generators, providing evidence that the activity level in the alpha and beta range - at least in part - contributes to the strength of the illusory auditory percept. This study corroborates the notion that alpha to beta activity in the auditory cortex is linked to functionally similar states, as has been proposed for visual, somatosensory and motor regions. Furthermore, our study provides certain theoretical implications for pathological auditory conscious perception (tinnitus). © 2014 Elsevier Inc.
Created from Fastlane, Scopus look-up
Keywords: Auditory illusion; Auditory perception; Gating-by-inhibition; Oscillatory activity; Similarity searchlight

Top-down modulation of the auditory steady-state response in a task-switch paradigm - Müller, Nadia; Schlee, Winfried; Hartmann, Thomas; Lorenz, Isabel; Weisz, Nathan (Frontiers in Human Neuroscience, 2009)
Auditory selective attention is an important mechanism for top-down selection of the vast amount of auditory information our perceptual system is exposed to. In the present study, the impact of attention on auditory steady-state responses is investigated. This issue is still a matter of debate and recent findings point to a complex pattern of attentional effects on the auditory steady state response (aSSR). The present study aimed at shedding light on the involvement of ipsilateral and contralateral activations to the attended sound taking into account hemispheric differences and a possible dependency on modulation frequency. In aid of this, a dichotic listening experiment was designed using amplitude-modulated tones that were presented to the left and right ear simultaneously. Participants had to detect target tones in a cued ear while their brain activity was assessed using MEG. Thereby, a modulation of the aSSR by attention could be revealed, interestingly restricted to the left hemisphere and 20 Hz responses: contralateral activations were enhanced while ipsilateral activations turned out to be reduced. Thus, our findings support and extend recent findings, showing that auditory attention can influence the aSSR, but only under specific circumstances and in a complex pattern regarding the different effects for ipsilateral and contralateral activations. © 2009 Müller, Schlee, Hartmann, Lorenz and Weisz.
Created from Fastlane, Scopus look-up
Keywords: ASSR; Attention; MEG; Suppression

You can't stop the music: Reduced auditory alpha power and coupling between auditory and memory regions facilitate the illusory perception of music during noise - Müller, Nadia; Keil, Julian; Obleser, Jonas; Schulz, Hannah; Grunwald, Thomas; Bernays, Rene-Ludwig; Huppertz, Hans-Juergen; Weisz, Nathan (NeuroImage, 2013)
Our brain has the capacity of providing an experience of hearing even in the absence of auditory stimulation. This can be seen as illusory conscious perception. While increasing evidence postulates that conscious perception requires specific brain states that systematically relate to specific patterns of oscillatory activity, the relationship between auditory illusions and oscillatory activity remains mostly unexplained. To investigate this we recorded brain activity with magnetoencephalography and collected intracranial data from epilepsy patients while participants listened to familiar as well as unknown music that was partly replaced by sections of pink noise. We hypothesized that participants have a stronger experience of hearing music throughout noise when the noise sections are embedded in familiar compared to unfamiliar music. This was supported by the behavioral results showing that participants rated the perception of music during noise as stronger when noise was presented in a familiar context. Time-frequency data show that the illusory perception of music is associated with a decrease in auditory alpha power pointing to increased auditory cortex excitability. Furthermore, the right auditory cortex is concurrently synchronized with the medial temporal lobe, putatively mediating memory aspects associated with the music illusion. We thus assume that neuronal activity in the highly excitable auditory cortex is shaped through extensive communication between the auditory cortex and the medial temporal lobe, thereby generating the illusion of hearing music during noise. © 2013 Elsevier Inc.
Created from Fastlane, Scopus look-up
Keywords: Alpha; Auditory imagery; Memory; Phase synchrony